2015
DOI: 10.1017/s1368980015000269
|View full text |Cite
|
Sign up to set email alerts
|

Rising trends of obesity and abdominal obesity in 10 years of follow-up among Tehranian adults: Tehran Lipid and Glucose Study (TLGS)

Abstract: Objective: Some recent studies have shown stablity or declining trends in obesity while others still report increasing trends. The present study aimed to investigate the trends of obesity and abdominal obesity in Tehranian adults during a median follow-up of 10 years. Design: Prospective cohort study. Setting: Community-based data collection from the Tehran Lipid and Glucose Study (TLGS). Subjects: Participants from four phases of the TLGS from 1999 to 2011 (n 10 368), aged ≥20 years. Results: The crude preval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 46 publications
(99 reference statements)
2
15
0
Order By: Relevance
“…In addition, it was shown that a sedentary lifestyle is prevalent in Iranian population, which is a well-documented risk factor for developing obesity (6). These results are consistent with the systematic review study and indicated that the trends of obesity is rapidly rising in both sexes and all social levels in population, which calls for urgent preventive public health strategies to educate and empower the community members, specially mothers and housewives for modifying obesity in families (1,5). The newest report from the TLGS revealed that after a median of 8-year follow up, the incidence of obesity (body mass index = BMI ≥ 30) was 31.3% (CI: 29.9% -32.7%) among the non-obese population, which was 38.1% (CI: 36.2% -40.1%) in women and 23.4% (CI: 21.6% -25.3%) in men.…”
Section: The Prevalence Of Obesity In Iransupporting
confidence: 75%
See 1 more Smart Citation
“…In addition, it was shown that a sedentary lifestyle is prevalent in Iranian population, which is a well-documented risk factor for developing obesity (6). These results are consistent with the systematic review study and indicated that the trends of obesity is rapidly rising in both sexes and all social levels in population, which calls for urgent preventive public health strategies to educate and empower the community members, specially mothers and housewives for modifying obesity in families (1,5). The newest report from the TLGS revealed that after a median of 8-year follow up, the incidence of obesity (body mass index = BMI ≥ 30) was 31.3% (CI: 29.9% -32.7%) among the non-obese population, which was 38.1% (CI: 36.2% -40.1%) in women and 23.4% (CI: 21.6% -25.3%) in men.…”
Section: The Prevalence Of Obesity In Iransupporting
confidence: 75%
“…Results from a previous investigation on 10 368 individuals in Tehran Lipid and Glucose study (TLGS) demonstrated that the raw prevalence of obesity and abdominal obesity increased from 23.1% and 47.9% in 1999 to 34.1% and 71.1% in 2011, respectively (5). In addition, it was shown that a sedentary lifestyle is prevalent in Iranian population, which is a well-documented risk factor for developing obesity (6).…”
Section: The Prevalence Of Obesity In Iranmentioning
confidence: 98%
“…Examining the rising trends of obesity and central obesity in the TLGS cohort, a related different pattern of rising between the two entities has been previously reported by our colleagues (26). Along with low physical activity and unhealthy diet, ecological characteristics of Tehran metropolis, which impose further unhealthy changes on life style and eating behavior of its inhabitants, might provide some explanation.…”
Section: Discussionsupporting
confidence: 57%
“…We have previously demonstrated that the increasing trend for obesity and abdominal obesity is more dramatic in Iranian men, aged 20-39 years [23]. Whether one could conclude that gender-specified metabolic effects might surmount the metabolic consequences of obesity remains a matter of debate.…”
Section: Discussionmentioning
confidence: 99%